Optimasi Pembuatan Heat Sealable Film dari Kolang-Kaling sebagai Bahan Kemasan - Sandi, Olifia Mutiara; Muhandri, Tjahja; Suyatma, Nugraha Edhi (Jurnal Teknologi dan Industri Pangan, 2024)
The sugar palm fruit (Arenga pinnata Merr.) has a great potential to be widely used in food industries due to its galactomannan that is able to form stable gels at high temperatures and produce excellent film properties. This study aimed to determine the optimum formula of edible films made from sugar palm fruit blended with carboxymethyl cellulose (CMC), beeswax, and glycerol, and then used them as food packaging. The independent variables included CMC concentration was 2–4% (w/v), beeswax concentration was 0.5–2% (w/v) and glycerol concentration was 1–2% (v/v). Sugar palm fruit 10 g and 100 mL of distilled water were set as fixed variables. The quality of the films was observed including thickness, heat sealability, water vapor transmission rate (WVTR), and solubility. The optimum formula was achieved as follows: 3.11% (w/v) CMC, 2.00% (w/v) beeswax, and 1.00% (v/v) glycerol. The optimum formula of edible film was thickness of 0.15 mm, heat sealability of 115.51 N/m, WVTR value of 2.86 g/m2/h, and solubility of 75.61%. Based on the characteristics of dissolution time test showed that the edible pouch took 2.5 min to dissolved.